Spatial Pattern Analysis of Dating Status as a Risk Factor on Adolescent Sexual Activity in Surabaya, Indonesia - Qurniyawati, Eny; Husnina, Zida; Sari, Jayanti Dian Eka; Azzahra, Asma; Shabrina, Izzah Nur (Althea Medical Journal, 2025)
Background: Many adolescents misinterpret the definition of sexual activity, which is only generalized as having sex. In fact, many other activities can trigger the emergence of sexually transmitted infections. Therefore, this study aimed to analyze various factors that influence the occurrence of sexual activity in adolescents.Methods: This study used a cross-sectional analytical design with non-probability sampling involving 152 active college students aged 18-24 years from Surabaya, Indonesia. Data was collected using a questionnaire about their experiences of sexual activity at a young age. The questionnaire was distributed online in July–August 2023. The data obtained was analyzed using the chi-square test and simple logistic regression. Then, Q-GIS software was used to describe data spatially. Results: Dating relationship status had an association with the occurrence of sexual activity (p-value= 0.00; OR: 8.84; 95%CI: 3.34 - 23.40). Spatial data showed that sexual activity of students in the eastern region of Surabaya City had a relatively high rate compared to other regions. Conclusion: Dating relationship status is associated with sexual activity. This study also shows that students who have ever dated and who have had sexual relations is directly proportional in each region in Surabaya. Awareness and education of adolescents about healthy sexual activities should be increased to protect them from the negative impacts of premarital sex.